The Effectiveness of Acupressure and Smart Gymnastic on Fasting Blood Sugar Levels among Patients with Type II Diabetes Mellitus - Dian Apri Nelyanti; Ta’adi Ta’adi; M. Choiroel Anwar (Alta Dharma Publisher, 2020)
Diabetes mellitus (DM) is a glucose metabolism disease characterized by an increase in blood sugar levels and impaired metabolism of fats, protein, and carbohydrates due to a lack of the hormone insulin, both absolutely and relatively. Alternative treatment of diabetes mellitus with complementary therapies, namely acupressure and smart gymnastic, can improve the fasting blood sugar level. This study aims to determine the effectiveness of acupressure and smart gymnastic on fasting blood sugar levels among patients with type II diabetes mellitus. True experimental study pretest and post-test with non-equivalent control group design were applied in this study. Repeated Measure, ANOVA test, showed a significant difference with the mean fasting blood sugar level p-value 0.000 (<0.05). The intervention group is better at lowering fasting blood sugar levels than control group 1 and control group 2 seen from the higher value difference. Conclusion of acupressure therapy with smart gymnastics three times a week for four weeks effectively reduces fasting blood sugar level in a patient with type II diabetes mellitus. This study can be used as a reference for further research, with a larger sample size, controlling the patient's diet, and a longer duration of intervention, so that the results obtained are more valid.